Prioritising Key Concepts for informed health choices in cancer: An evidence-based online educational programme - Mengqi Li; Declan Devane; Claire Beecher; Maura Dowling; Austin G. Duffy; Caitriona Duggan; David Robert Grimes; Avril Kennan; Claire Kilty; Allen Nsangi; Andrew D. Oxman; Derek C. Stewart; et al. (PEC Innovation)
Objective: The overabundance of health misinformation has undermined people's capacity to make evidence-based, informed choices about their health. Using the Informed Health Choices (IHC) Key Concepts (KCs), we are developing a two-stage education programme, Informed Health Choices-Cancer (IHC-C), to provide those impacted by cancer with the knowledge and skills necessary to think critically about the reliability of health information and claims and make well-informed choices. Stage 1 seeks to prioritise the most relevant Key Concepts. Methods: A project group and a patient and carer participation group completed a two-round prioritisation process. The process involved disseminating pre-reading materials, training sessions, and a structured judgement form to evaluate concepts for inclusion. Data from each round were analysed to reach a consensus on the concepts to include. Results: Fourteen participants were recruited and completed the first-round prioritisation. Fifteen participants undertook the second-round prioritisation. Nine Key Concepts were selected for the programme across five training sessions and two consensus meetings. Conclusion: The prioritised concepts identified represent the most pertinent aspects of cancer-related information for those impacted by the disease. By incorporating these concepts into educational materials and communication strategies, healthcare providers and organisations can potentially help cancer patients, survivors, and their loved ones to recognise and combat cancer-related misinformation more effectively. Innovation: This study introduces a participatory prioritisation process, which integrates the expertise of healthcare professionals with the insights of patients and carers, thereby enhancing the programme's relevance and applicability.